2013
DOI: 10.1007/978-94-007-6627-3_18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Acute Respiratory Tract Diseases Among Soldiers Deployed for Military Operations in Iraq and Afghanistan

Abstract: Respiratory diseases are one of the most common health problems among service personnel assigned to contemporary military operations which are conducted in areas characterized by adverse environmental conditions. This article reviews the results of the studies into the prevalence of acute respiratory tract diseases among soldiers of the Polish Military Contingent deployed to Iraq and Afghanistan. The article also discusses a number of factors which increase the prevalence of diseases diagnosed in the populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…However, this issue is not limited to U.S. military personnel. A study investigating Polish coalition soldiers also found acute respiratory tract diseases to be prevalent and correlated this finding with environmental factors, such as extreme temperature fluctuations, unsanitary conditions, and sand and dust storms [ Korzeniewski et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this issue is not limited to U.S. military personnel. A study investigating Polish coalition soldiers also found acute respiratory tract diseases to be prevalent and correlated this finding with environmental factors, such as extreme temperature fluctuations, unsanitary conditions, and sand and dust storms [ Korzeniewski et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…[8,15,16] A study from Kuwait showed that sandstorms have a significant impact on respiratory and asthma symptoms and hospital admissions. [17] High rates of respiratory symptoms (14%) as well as new-onset asthma among previously healthy soldiers (6.6%) were seen among soldiers post-deployment to Iraq and Afghanistan.…”
Section: Discussionmentioning
confidence: 99%
“…За даними раніше проведених досліджень, рівень захворюваності на гострий тонзиліт у військовослуж-бовців зростає в періоди, коли він також зростає й се-ред цивільного населення, також набагато частіше дане явище спостерігається в періоди оновлення особового складу внаслідок призову молодого поповнення чи під час ротації підрозділів на тактично важливих ділянках [8][9][10].…”
Section: оригінальні дослідження вступunclassified